Pemanfaatan Bahan Ajar Digital Sebagai Solusi Keterbatasan Buku Paket Akidah Akhlak di MA Plus Nurul Islam Sekarbela - Asih Pujinarti; Dedi Riyan Rizaldi; Rabiatul Hasanah; Nurul Yakin; Nilwan; Ziadatul Fatimah (Action Research Journal, 2026)
This study aims to find out how the use of digital teaching materials can be a solution to the limitations of package books in learning moral beliefs at MA Plus Nurul Islam Sekarbela. This study uses a qualitative approach with a case study method. The subjects of this study consist of teachers of moral beliefs and several students who are directly involved in the learning process based on digital teaching materials. Data was collected through interviews, observations, and documentation, then analyzed in a qualitative descriptive manner. The results of the study show that the use of digital teaching materials has a positive influence on increasing the effectiveness of learning moral beliefs. Teachers are able to use technology as an auxiliary medium to deliver material in a more interesting, efficient, and interactive manner. Students feel more motivated and understand the material easily because the digital teaching materials are equipped with supportive visual, audio, and video displays. The obstacles faced include limited internet networks, devices, and the level of digital literacy, but they can be overcome through the support of madrasah facilities and training for teachers. Thus, the use of digital teaching materials has proven to be an effective solution in overcoming the limitations of package books, and is able to create learning moral beliefs that are more interesting, meaningful, and in accordance with technological developments, without reducing the Islamic spiritual values contained in it